Analysis Pneumatic System of The Causes of Engine Bleed Trip on Boeing 737-900 ER Aircraft Using the Fault Tree Analysis (FTA) Method - Kurniawan, Muhammad Hadi; Adiputra, Bangga Dirgantara; Rahmawati, Fajar Khanif; Mulyani, Sri; Prattiwi, Elisabeth Anna (Vortex, 2025)
The Engine Bleed Air system is one of the primary systems in an aircraft and Its components include the Pressure Regulating Shutoff Valve (PRSOV), Bleed Air Regulator (BAR), High Stage Valve (HSV), High Stage Regulator (HSR), Precooler Control Valve (PCCV), and PCCV sensors 390 and 450. Any malfunction in these components can directly impact aircraft safety and flight operations. This research analyzes the performance failures of the system in regulating the temperature and pressure distributed by the bleed air system, particularly focusing on engine bleed trips. This study aims to determine the percentage of necessary component replacements in the air bleed engine system using the Fault Tree Analysis (FTA) method. Primary data is collected from aircraft maintenance databases and interviews. The percentage of main component replacements needed are: thermostat sensor 390 (42.3%), Precooler Control Valve (19.2%), Pressure Regulating Shutoff Valve (11.5%), and Bleed Air Regulator (7.7%). The remaining components account for the other percentages.